TRANSPARENCY AND ACCOUNTABILITY OF KARANGREJO VILLAGE GARUM DISTRICT BLITAR REGENCY ON MANAGEMENT OF VILLAGE FUNDS IN 2019 - Vembita Sapna Key; Diana Elvianita Martanti (Universitas Islam Balitar, 2020)
Village Funds are funds allocated in the APBN, intended for villages and are used to finance governance, implementation of development, community development, and community empowerment. In the management of village funds by the village government, it is obliged to implement them in a transparent and accountable manner so a clean and responsible village government can be realized, as well as the achievement of the goals and objectives of the disbursement of the village funds. This research aims to determine the transparency and accountability of village fund management conducted by the government of Karangrejo Village, Garum District, Blitar Regency in 2019. The data collection used was observation, interviews, documentation and literature study. The results of the study showed that the management of village funds carried out by the Karangrejo Village government in 2019 was from the planning stage to the accountability in accordance with the applicable laws or regulations. With the application of the siskeudes, Karangrejo Village government is greatly facilitated in the bookkeeping and financial reporting process which can be monitored and evaluated directly by the local government. It shows that the Karangrejo Village government is accountable. While in the context of transparency by the Karangrejo Village government, starting from the deliberation and structured planning to the reporting process carried out using digital information media that can be accessed by all village communities and also placed on the information boards at the Karangrejo Village office.